New challenges the establishment of district governmental offices and the regional public transport organising in Hajdú-Bihar county - Bói, Loránd (Acta Agraria Debreceniensis, 2013)
The re-establishment of historical district government offices in the Hungarian public administration system will ensure the availability of the provided public services on an integrated, citizen-friendly level. Reorganising of district borders and changing the district centres as well the settlement new administration services in the central cities will predictable restructure the citizens public transport attitudes. This study deals with the motivation, quantity and direction of the possible modifications on the public transport demand in Hajdú-Bihar County. The study goals to present the possible public transport organising interventions, and to find a balance between the changing demand and the regulation provided public transport instruments.